2012
DOI: 10.1371/journal.pone.0042381
|View full text |Cite
|
Sign up to set email alerts
|

Geological Substrates Shape Tree Species and Trait Distributions in African Moist Forests

Abstract: BackgroundUnderstanding the factors that shape the distribution of tropical tree species at large scales is a central issue in ecology, conservation and forest management. The aims of this study were to (i) assess the importance of environmental factors relative to historical factors for tree species distributions in the semi-evergreen forests of the northern Congo basin; and to (ii) identify potential mechanisms explaining distribution patterns through a trait-based approach.Methodology/Principal FindingsWe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 66 publications
4
103
2
5
Order By: Relevance
“…In general, fast-growing trees are light demanding and produce low-density wood as found by Rueda and Williamson (1992), van Gelder et al (2006) and Henry et al (2010). However other studies have shown that some pioneer light demanding tree species can, unexpectedly, have high wood density (e.g Lophira alata, Fayolle et al 2012) and this may be explained by wood composition and structure (Martínez-Cabrera et al 2009;Poorter et al 2010;Zanne et al 2010).…”
Section: Basic Wood Densitymentioning
confidence: 96%
“…In general, fast-growing trees are light demanding and produce low-density wood as found by Rueda and Williamson (1992), van Gelder et al (2006) and Henry et al (2010). However other studies have shown that some pioneer light demanding tree species can, unexpectedly, have high wood density (e.g Lophira alata, Fayolle et al 2012) and this may be explained by wood composition and structure (Martínez-Cabrera et al 2009;Poorter et al 2010;Zanne et al 2010).…”
Section: Basic Wood Densitymentioning
confidence: 96%
“…However, this has only recently arisen as a concern in the Congo Basin (Gourlet-Fleury et al 2011) where it has not yet been taken into account in forest management practices (N. Bayol personal communication). Large parts of the southern CAR and the northern Republic of Congo are characterized by ''Carnot'' sandstone, producing resource-poor soils associated with dense, slow-growing forest types (Fayolle et al 2012; Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…A homogenized geological map (Fayolle et al 2012) based on three national maps (Gazel 1956, Orstom 1967, Boulvert 1996 was used to identify areas of contrasting ''substrate fertility''. Geological types were characterized analogous to Gourlet-Fleury et al (2011).…”
Section: Environmental and Human Infrastructure Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…4.1). For example, in African forests, sandy soils, compared to clayey soils, had a higher abundance of species with high wood density that are more drought tolerant and better survive on sandy and resourcelimited soils (Fayolle et al 2012). In our study forest, disturbance due to logging treatments changed the trait composition of demographic groups towards more acquisitive trait values (e.g., high specific leaf area and low wood density) that are typical of pioneer species that benefit from higher light levels (Carreño-Rocabado et al 2012).…”
Section: Introductionmentioning
confidence: 99%